CREATIVE BIOGRAPHY OF DESIGNER VOLODYMYR NESMYAN: BETWEEN MEMORY AND FREEDOM - Ніколаєва, Т. В.; Кокоріна, Г. В. (Art and Design, 2018)
Purpose was to systematize the facts of the biography of the famous Ukrainian designer Volodymyr Nesmiyan and determine his role in the development of Ukrainian fashion, analysis of organizational projects and aesthetic views. Methods of historical-chronological and comparative analysis, systematization of visual sources, interview method are used. The research material consists of sketches and photographs from the personal archives of V. Nesmiyan, periodicals of the 1950–1990s, interviews with V. Nesmiyan and his collaborators. From a scientific point of view, information about the activities of the prominent Ukrainian designer and inventor V. Nesmiyan, the structured results of his creative heritage was collected and analyzed. The creative biography is considered in the chronological aspect: the facts of professional activity are described, the motivation and results of the research are described, the essence of organizational and pedagogical projects is analyzed. The professional biography of the designer is considered in the context of the specific problems of the Ukrainian fashion of the twentieth century.